The Effect Of Pregnancy Exercise Education And Supervision On Anxiety In Third-Trimester Pregnant Women (International Forum of Researchers and Lecturers, 2025)
Background: Pregnancy is a natural physiological process that lasts approximately 40 weeks. In the third trimester, pregnant women experience physical and psychological stress due to hormonal changes, which can trigger anxiety before childbirth. This anxiety is often caused by concerns about complications, pain during childbirth, and fear of caring for the baby. Data shows that approximately 30% of pregnant women globally and 28.7% in Indonesia experience anxiety, even reaching 35% in South Sulawesi. Prenatal education and light exercise such as pregnancy exercises have been shown to reduce anxiety and increase readiness for childbirth. Family support also plays an important role in maintaining the mental health of pregnant women. Objective: This study was conducted at the Dahlia Community Health Center in Makassar City to determine the relationship between education and mentoring in pregnancy exercises with the level of anxiety of pregnant women in the third trimester. Research Method: The method used is a quantitative research type, through a descriptive correlation approach and a cross-sectional research design to understand the correlation between the relationship of pregnancy exercises with the level of anxiety of pregnant women in the third trimester in facing childbirth. Results: The chi-square statistical test yielded a value of ρ=0.118>(ρ=0.05), indicating no relationship between prenatal exercise and anxiety levels. Meanwhile, the Mann-Whitney test showed a difference in anxiety levels between the group that participated in prenatal exercise and the group that did not participate in prenatal exercise (ρ=0.046). Conclusion: There is an effect of prenatal exercise education and support on anxiety in third-trimester pregnant women.